1997
DOI: 10.1002/(sici)1098-108x(1997)21:4<385::aid-eat12>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Eating disturbances and outcome of gastric bypass surgery: A pilot study

Abstract: Objective We examined how the outcome of gastric bypass surgery (GBP) was effected by the interaction between presurgery eating disturbance status and length of time since surgery. Method: Subjects were recruited from a list of patients who received GBP in the last 3 years. Twenty‐seven patients 20.8 ± 11.0 months postsurgery were interviewed. Results: Both current eating disturbance status and weight regain were predicted by the interaction between presurgical eating disturbance status and length of time sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(59 citation statements)
references
References 5 publications
3
54
0
2
Order By: Relevance
“…At 12-months post-surgery, none of the patients reported binge eating at the diagnostic threshold frequency specified by the DSM-IV-TR for BED; 8.8% reported infrequent binge eating (i.e., less than once per week) and only one patient (0.7%) reported binge eating weekly. These substantial improvements in binge eating support previous reports of a near remission of binge eating symptoms following surgery 17, 25, 26.…”
supporting
confidence: 88%
“…At 12-months post-surgery, none of the patients reported binge eating at the diagnostic threshold frequency specified by the DSM-IV-TR for BED; 8.8% reported infrequent binge eating (i.e., less than once per week) and only one patient (0.7%) reported binge eating weekly. These substantial improvements in binge eating support previous reports of a near remission of binge eating symptoms following surgery 17, 25, 26.…”
supporting
confidence: 88%
“…This suggestion is consistent with the restraint-theory, which attributes overeating to dieting: attempts to restrict food intake initiate physiological defenses, such as lowering the metabolic rate and persistent hunger, which threaten dieting efforts 24. Like others, we did find a decrease in emotional and external eating,4143 and that improvements in eating behaviors waned over time 41,43. Also, our findings are partly in line with another study comparing patients’ eating behavior to normative scores; however, as to restrained eating, this study found no significant differences 42…”
Section: Discussionsupporting
confidence: 91%
“…However, various studies provide conflicting results and no clear predictors [94, 95]. Some studies have found poor weight loss postoperatively in the presence of preoperative personality disorders [96], mood disorders [9799], or eating disorders [100103]. However, there are also many studies that could not find any relationship between the presence or absence of preoperative psychiatric disturbances and weight loss after surgery [57, 104108].…”
Section: Impact Of Psychopathology On Outcomes Of Bariatric Surgerymentioning
confidence: 99%